Communication of the Cooperative Identity focused on Social Responsibility. Beyond Commercial Advertising - García Villamizar, Clara Inés (2017)
Based on a case study that is supported on the inferential statistics of a leading Colombian cooperative, a proposal is made for the analysis of correspondence between image and corporate identity, and the communication´s impact on the perception of its associates and employees. It is particularly noted that the associates have a very favorable image of the institution, but a high lack of knowledge of their identity. On the contrary, in the employees there is correspondence between the recognition of a favorable image of the company and the identity of the same thanks to a greater focus towards corporate communication.